The Effect of Fermentation Soybean and Cassava Waste by Rhizopus sp in Merino Sheep Concentrate to Feed Convertion and Income Over Feed Cost - maritius herpin syukur (Jurnal Sains Peternakan, 2015)
ABSTRACT This study aims to determine the feed conversion and income over feed cost extra pulp fed soya and cassava fermented. materi used were 12 male merino sheep with an average weight of 30 kg. Experimental method which consists of 4 treatments with 3 replications livestock. The treatment P0 control; P1 concentrate 90% + 10%; P2 concentrate 80%+20%; P3 concentrate 70%+30%. The variables were observed in this study include feed conversion and income over feed cost. Results of this study that the addition of soy pulp and onngok fermented in concentrate feed did not significantly affect feed conversion (P<0.05) and income over feed cost (P <0.01). The average feed conversion P0, P1, P2, P3 are respectively 5286.40; 5922.90; 3598; 51 and 2578.44 and the average value P0 income over feed cost 243 224; 173 339; 345 113; 576 885. It was concluded that the use of fermented soybean and cassava dregs did not significantly affect feed conversion but it can increase the value of income over feed cost.Keywords: Fermentation, Feed Convertion, Income Over Feed Cost